Central line-associated bloodstream infection related with umbilical vein catheterization and peripherally inserted central catheter in preterm infants: a meta-analysis and systematic review - Sandinirwan, Indra; Leo, Henry; Muslim, Bani; Hasanah; Karina, Permata Putri (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Central line-associated bloodstream infection (CLABSI) is a serious complication in preterm infants undergoing catheterization, including umbilical vein catheterization (UVC) and peripherally inserted central catheter (PICC) placement. This study aimed to compare the occurrence rate of CLABSI in preterm infants associated with UVC and PICC. METHODS We conducted a systematic review and meta-analysis of studies published from 2000 to 2023 using a random effects model from 3 databases (PubMed, ScienceDirect, and Google Scholar). This study was registered with PROSPERO (CRD42023416471). RESULTS Of 10 articles included in the systematic review, 2 were randomized controlled trials, 3 were prospective studies, and the rest were retrospective. A total of 3,962 UVCs and 2,922 PICCs were incorporated in the meta-analysis. The incidence rate of CLABSI in the UVC group was lower than that in the PICC group (1.23 versus 3.03 per 1,000 catheter days). However, the odds of developing CLABSI for infants with a UVC compared to those with a PICC were not statistically significant (odds ratio: 0.88, 95% confidence interval: 0.54–1.42). CONCLUSIONS UVCs had a lower incidence rate of CLABSI than PICCs. Therefore, additional prospective studies are required to confirm these results.